2015
DOI: 10.1016/j.scienta.2015.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gum arabic coating combined with calcium chloride on physico-chemical and qualitative properties of mango (Mangifera indica L.) fruit during low temperature storage

Abstract: a b s t r a c tEffect of gum arabic (GA) 10% and calcium chloride (CA) 3% on the physiological and biochemical properties of mango (Mangifera indica L. CV. Choke Anan) fruits stored at 6 ± 1 • C and 90 ± 3% relative humidity for 28 days and then transferred to 25 ± 2 • C for 5 days shelf life were investigated. Significant (P ≤ 0.05) differences were observed in fruits treated with GA 10% and CA 3% as compared to control. The combined treatment of CA 3% + GA 10% significantly alleviated the increase in decay i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
94
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(118 citation statements)
references
References 38 publications
19
94
0
5
Order By: Relevance
“…Gum arabic, due to its certain film forming and antimicrobial characteristics, might have prevented pathogen attack, thereby reducing decay incidence. Our results are in line with the findings of Khaliq et al [47] who had reported a reduced decay incident in gum arabic coated mango fruit. On the other hand, coated fruit exhibited significantly lower CI than untreated (uncoated) bell pepper fruit.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Gum arabic, due to its certain film forming and antimicrobial characteristics, might have prevented pathogen attack, thereby reducing decay incidence. Our results are in line with the findings of Khaliq et al [47] who had reported a reduced decay incident in gum arabic coated mango fruit. On the other hand, coated fruit exhibited significantly lower CI than untreated (uncoated) bell pepper fruit.…”
Section: Discussionsupporting
confidence: 94%
“…Previous findings showed that gum arabic coating resulted in higher TA in tomatoes [46]. Our results are in confirmation with the findings of Khaliq et al [47] where 10% gum arabic alone or in combination with 3% calcium exhibited higher TA by preventing degradation of organic acids in mango fruit during cold storage.…”
Section: Discussionsupporting
confidence: 93%
“…Decrease in firmness of fruits is due to pectinase and hydrolase enzyme activity that leads to degradation in cell structure, cell wall composition and inter and intracellular materials (Seymour et al, 1993). Inhibition of loss of firmness by edible coatings has been reported for various fruits including 10% GA in mango (Khaliq et al, 2015), 10 and 15% GA in tomato (Ali et al, 2010), combined treatment of GA and chitosin in banana (Maqbool et al, 2011). In this study, GA 5% and 10% coated fruits showed higher firmness than the control fruits and this may be due to thick coating which created a modified atmosphere around the fruit surface as a result reduced changes in pectin substances and activity of cell wall degrading enzymes.…”
Section: Physical Parametersmentioning
confidence: 50%
“…It is a mixture of polysaccharides and glycoproteins used in industries for film forming, emulsification and encapsulation properties. Earlier, shelf life has been extended by applying gum arabic coating in tomato (Ali et al, 2010), mango (Khaliq et al, 2015), sweet cherry (Mahafaudi and Hamdi, 2014) and green chillies (Chitravathi et al, 2014). Therefore, the aim of this study was to understand the effect of gum arabic coating on extending shelf life, retaining freshness and quality of guava fruits during storage under ambient conditions.…”
Section: Issn: 2319-7706 Volume 7 Number 05 (2018)mentioning
confidence: 99%
“…The Arabic gum has broad relevance in the food (Chen et al, 2015;Khalid et al, 2014), pharmaceutical (Musa et al, 2015) and cosmetic industry (Khaliq et al, 2015). Polysaccharides such as Arabic gum, cashew gum and others can still move numerous research papers, involving studies of extraction, identification and characterization processes, properties, biological activities and applications (Yang & Zhang, 2009).…”
Section: Introductionmentioning
confidence: 99%